Technopreneurial Strategies Using Digitalization and Innovation to Strengthen Student Loyalty - Maduwinarti, Ayun; Mahendra, I.G.N. Andhika; Cahyono, Dwi; Gusmao, Cristino (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study aims to explore the interaction between service quality and digital transformation in reconstructing students' loyalty in higher education, with a specific focus on academic and non-academic services at Indonesian universities. The theoretical framework integrates service quality dimensions, digital transformation concepts, and loyalty models to provide a comprehensive understanding of how these factors shape students' loyalty in the digital era. Utilizing a Grounded Theory approach, data were collected through in-depth interviews with students, faculty members, and administrative staff. Data analysis involved open coding, axial coding, and selective coding to develop Digital-Service Synergy Theory explaining the loyalty reconstruction process. Findings indicate that while both service quality and digital transformation significantly influence student loyalty, their interaction creates a more complex dynamic that determines overall satisfaction and loyalty. Key factors influencing effectiveness include e-learning system quality, instructor responsiveness, technical support, and digital anxiety management. The study provides insights into optimizing the synergy between traditional service quality and digital transformation to enhance student loyalty and offers practical solutions for implementation challenges in higher education institutions.